Sistema de control y gestión de inventarios en el Taller Industrial Espinoza de la ciudad de Babahoyo, periodo 2020-2021. - Barragán Espinoza, Roddy Steveen (2023)
The purpose of this case study is to carry out an analysis, issue a diagnosis, develop a control and management system for the correct management of inventories in the Espinoza industrial workshop in the city of Babahoyo, aimed at optimizing the main resource that is time in terms of prices and performance of manufacturing projects for all kinds of wooden furniture for the home, the same as for several years, does not have adequate control of the materials it needs and has available for each work carried out. The Industrial Espinoza workshop is presided over by Mr. Espinoza Corrales Vidal, whose ID number is 0901467845001. He is required to submit VAT declarations every six months, and who has great patience, care, passion, and commitment to make works of art with wood, from a small sideboard, even a whole kitchen with drawers, shelves, space savers, doors, etc. However, despite the difficulty regarding the inventory control system, which produces a constant loss in the contracts that the workshop has executed successfully, it is for this reason that the present work is developed to be able to identify, evaluate and implement an inventory system, coherent and effective, easy to understand for the user. Said study is governed under the lines of research of financial, administrative, tax, audit, control management as the main line in which it is framed in the sub-line of financial, tax and social commitment management.